Crystal Structure Features of CsPbBr3 Perovskite Prepared by Mechanochemical Synthesis - Lopez, Carlos Alberto (2020)
We present a mechanochemical procedure, with solvent-free, green-chemistry credentials, to grow all-inorganic CsPbBr3 perovskite. The crystal structure of this perovskite and its correlations with the physicochemical properties have been studied. Synchrotron X-ray diffraction (SXRD) and neutron powder diffraction (NPD) allowed us to follow the crystallographic behavior from 4 to 773 K. Unreported features like the observed negative thermal expansion of the b unit-cell parameter stem from octahedral distortions in the 4-100 K temperature range. The mechanochemical synthesis was designed to reduce the impact energy during the milling process, leading to a defect-free, well-crystallized sample characterized by a minimum unit-cell volume and octahedral tilting angles in the low-temperature orthorhombic perovskite framework, defined in the Pbnm space group. The UV-vis diffuse reflectance spectrum shows a reduced band gap of 2.22(3) eV, and the photocurrent characterization in a photodetector reveals excellent properties with potential applications of this material in optoelectronic devices.